Is Truly Trustworthiness of Celebrity Endorsement Effect on Online Purchase Intention: A Study on Online Travel Agency Customers - Syanda Cicit Daradinanti; Rini Kuswati (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze whether the trustworthiness of celebrities used in endorsements affects online purchase intentions at Online Travel Agencies. In today's digital era, the use of celebrities as endorsers is a common marketing strategy, but its effectiveness in the context of Online Travel Agencies still needs to be studied more deeply. This study empirically examines the effect of celebrity trustworthiness on purchase intentions through an Online Travel Agency, taking into account other factors such as information usefulness, information adoption, attractiveness, and expertise. The research methodology uses quantitative, this study collects data from online travel agency customers through surveys with questionnaires distributed online to consumers who have used or plan to buy Online Travel Agency products. Data analysis was carried out using Smart PLS (PLS-SEM) to test the research hypothesis. The results of the study are expected to provide valuable insights for Online Travel Agency marketers in designing effective endorsement strategies, as well as contribute to the development of marketing theory related to celebrity endorsement and consumer behavior in the context of e-commerce, especially the travel industry.